Meningkatkan Perilaku Pro Lingkungan Peserta Didik Menggunakan Model Pembelajaran Project Based Learning - Azrai, Eka Putri; Heryanti, Erna; Ramadhani, Verdiana; Ilyas, Marlina (Biosfer: Jurnal Pendidikan Biologi, 2024)
The waste problem that continues to increase throughout the pandemic shows that humans are still carrying out activities that only benefit themselves without caring about nature. This destructive behavior can be changed through an educational process that increases pro-environmental behavior. The purpose of this study is to determine the effectiveness of the project-based learning model implementation of high school students on environmental change material to improve students’ pro-environmental behavior. The method used is quasi-experimental using the Discovery Learning model in the control class and the Project Based Learning model in the experimental class. This research was conducted at a senior high school in Jakarta. The research sample consisted of 60 students who were selected by random sampling with 30 students in each class. The pro-environment behavior instrument was adapted from Kasier and Wilson consisted of 40 statements. Data analysis used t-test and the results showed a significance value of 0.002. It can be concluded that using project-based learning model can improve the pro-environmental behavior of high school students. The N-Gain test was also carried out, and turns out the effectiveness of the learning model in both classes was low. This can be happened because teachers are still not used to the Project Based Learning model. In the future, it is still necessary to conduct research involving other factors that affect pro-environmental behavior in the application of learning in schools.